EVALUASI KELENGKAPAN PERALATAN PRAKTIK INSTALASI TENAGA LISTRIK SMK (Studi Kasus di SMK Taruna Bangsa Bekasi) - Ahmad Ramadhan Putra; Soeprijanto; Massus Subekti (Journal of Electrical Vocational Education and Technology, 2020)
ABSTRACT This research aims to evaluate the completeness level of equipments standard of engineering elevtrical power’s installation in Taruna Bangsa Vocational High School, which was ruled in the Ministry of Education’s rules No. 1 2019 and The National Standardization Agency of Indonesia No. 1103-P2-18/19 about the Verification Instruments of Vocational High School, The Organizer of Vocational Practice Exam 2018/2019.This is an evaluative research using a quantitative descriptive approach. The evaluative model used was a discrepancy evaluation model, which was developed by M. Provus. The variable in this research is the equipment of electricity power’s installation practice in Taruna Bangsa Vocational High School Bekasi. The methods of collecting the data were three types: observation method, documentation, and interviews. The instrument used was collecting the data using observation paper and list of matched documentation. The analysis technique used in this research is rating scale.The result shows that the reaching of equipment of elecrical power installation practice in Taruna Bangsa Vocational High School Bekasi in academic year of 2018/2019 was categorized as complete with the 89,36%. percentages. The completeness was reviewed from the equipments in practice room as complete (88.5%), the equipments of learning media room is complete (100%), the main equipment of practice is complete (93%), and for the main substance of practice room is complete (88.2%),also for the equipment support is compelete (77.1%). ABSTRAK Penelitian ini bertujuan mengevaluasi tingkat kelengkapan standar peralatan praktik teknik instalasi tenaga listrik di SMK Taruna Bangsa Bekasi yang diatur dalam Permendiknas No. 1 tahun 2019 dan Badan Standar Nasional Pendidikan No. 1103-P2-18/19 mengenai Instrumen Verifikasi SMK Tentang Penyelenggara Ujian Praktik Kejuruan Tahun 2018/2019. Penelitian ini merupakan penelitian evaluatif dengan menggunakan pendekatan deskriptif kuantitatif. Model evaluasi yang digunakan adalah model evaluasi kesenjangan (discrepancy evaluation model) yang dikembangkan oleh M. Provus. Variabel penelitian ini adalah peralatan praktik teknik instalasi tenaga listrik di SMK Taruna Bangsa Bekasi. Metode pengumpulan data yang digunakan dalam penelitian ini ada tiga macam, yaitu metode observasi, dokumentasi dan wawancara. Instrumen pengumpulan data menggunakan lembar observasi dan daftar cocok dokumentasi. Teknik analisis data yang digunakan dalam penelitian ini adalah rating scale. Hasil penelitian menunjukkan bahwa tingkat ketercapaian kelengkapan peralatan praktik teknik Instalasi Tenaga Listrik di SMK Taruna Bangsa Bekasi pada tahun ajaran 2018/2019 dikategorikan sangat lengkap dengan persentase 89,36%. Kelengkapan di tinjau dari perabotan ruang praktik yaitu 88.5% (sangat lengkap), media pembelajaran ruang praktik 100% (sangat lengkap), peralatan utama praktik 93% (sangat lengkap), bahan utama ruang praktik 88.2% (sangat lengkap) dan peralatan pendukung ruang praktik 77.1% (lengkap).